PROFESIONALISME GURU PENJASKES DALAM MENINGKATKAN MOTIVASI BELAJAR DI SMP NEGERI 3 BATUSANGKAR - Muhammad Hafizh (Sekolah Tinggi Ilmu Tarbiyah (STIIT) Ahlussunnah Bukittinggi, 2021)
Penjaskes learning is one form of learning as a support for fitness and health for students in Midle school lima kaum batusangkar, because it is supported by the surrounding community conditions that support sports programs with volleyball, sepak takraw, badminton and soccer. on this basis sports teachers at midle school Batusangkar designed a structured sports program for students with sports and learning formulations with the aim of increasing learning motivation that was balanced between physical fitness and good health to receive effective and efficient learning so that learning goals were achieved. qualitative descriptive research with three variables, namely planning, implementation and assessment of learning skills in motivating student learning. The results of this study were found in public junior high school 3 cage stones found and concluded that the education program activities in theory and practice were formatted in an interesting and joyful manner so that the spirit of exercise arose and resulted in strong learning motivation in 3 Batusangkar Midle Scholl